2011
DOI: 10.2337/db10-0795
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I– and MDA5-Initiated Innate Immunity Linked With Adaptive Immunity Accelerates β-Cell Death in Fulminant Type 1 Diabetes

Abstract: OBJECTIVEThe contribution of innate immunity responsible for aggressive β-cell destruction in human fulminant type 1 diabetes is unclear.RESEARCH DESIGN AND METHODSIslet cell expression of Toll-like receptors (TLRs), cytoplasmic retinoic acid–inducible gene I (RIG-I)-like receptors, downstream innate immune markers, adaptive immune mediators, and apoptotic markers was studied in three autopsied pancreata obtained 2 to 5 days after onset of fulminant type 1 diabetes.RESULTSRIG-I was strongly expressed in β-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 24 publications
(33 reference statements)
6
97
1
Order By: Relevance
“…Studies of gene-deficient mice indicate that RLRs play an important role in antiviral response [22][23][24]. We have demonstrated significant hyper-expression of RLRs in islet cells of patients with fulminant type 1 diabetes [8,9]. MDA5 was strongly expressed in islet cells (including β-and α-cells) of fulminant type 1 diabetic pancreata.…”
Section: Enterovirus In the Pancreasmentioning
confidence: 74%
See 4 more Smart Citations
“…Studies of gene-deficient mice indicate that RLRs play an important role in antiviral response [22][23][24]. We have demonstrated significant hyper-expression of RLRs in islet cells of patients with fulminant type 1 diabetes [8,9]. MDA5 was strongly expressed in islet cells (including β-and α-cells) of fulminant type 1 diabetic pancreata.…”
Section: Enterovirus In the Pancreasmentioning
confidence: 74%
“…The human TLR multigene family comprises 10 members, with TLR2, -3, -4, -7, and -8 considered to be of importance in the recognition of structural components of RNA viruses, including viral doublestranded RNA, single-stranded RNA, and surface glycoproteins [30]. We showed that both TLR3 and TLR4 were expressed in MNCs that had infiltrated islets of fulminant type 1 diabetic pancreata, but not SPIDDM patients or non-diabetic controls [8,9]. The frequencies of islets with infiltrating MNCs expressing TLR3 and TLR4 were 11.7% and 4.3%, respectively, although almost no islet with MNCs expressing TLR3 or TLR4 was recognized in pancreata of non-diabetic controls or SPIDDM patients.…”
Section: Enterovirus In the Pancreasmentioning
confidence: 86%
See 3 more Smart Citations